Dual-Catalysis-Enabled Construction of Vicinal Stereogenic Centers through Diastereo- and Enantioselective Allylic Substitution - Yang, Kai; Chen, Lu; Su, Bo (Synthesis, 2024)
Vicinal stereogenic centers represent prevalent structural motifs in organic synthetic chemistry, and their construction poses a longstanding challenge. Transition-metal-catalyzed asymmetric allylic substitution has become a well-established enantioselective C–C bond-forming reaction. When these reactions involve a prochiral nucleophile and an allylic electrophile with a terminal substituent, the creation of vicinal stereogenic centers becomes feasible. However, despite remarkable achievements having been accomplished, realizing this transformation with precise control over both the enantio- and diastereoselectivity remains a significant challenge. To address the stereoselective challenges, the introduction of a second catalyst to the transition-metal-catalyzed asymmetric allylic alkylation to control the diastereoselectivity during C–C bond formation has proven particularly fruitful. In this short review, we aim to highlight recent advances in dual catalysis that enable diastereo- and enantioselective allylic substitutions.1 Introduction2 Construction of Vicinal Stereogenic Centers by Organo and Metal Dual Catalysis2.1 Chiral Phase-Transfer Catalysis and Transition-Metal Dual Catalysis2.2 Chiral Amine and Transition-Metal Dual Catalysis2.3 NHC and Transition-Metal Dual Catalysis2.4 Chiral Aldehyde and Transition-Metal Dual Catalysis2.5 Chiral Lewis Base and Transition-Metal Dual Catalysis3 Construction of Vicinal Stereogenic Centers by Metal and Metal Dual Catalysis3.1 Lewis Acidic Metal and Iridium Dual Catalysis3.2 Lewis Acidic Metal and Palladium Dual Catalysis3.3 Palladium and Ruthenium Dual Catalysis3.4 Other Advancements in the Construction of Vicinal Stereogenic Centers through Synergistic Bimetallic Catalysis Enabling Asymmetric Allylic Alkylation4 Conclusions and Future Outlook
Keywords: transition-metal-catalyzed allylic alkylation; asymmetric allylic substitution; vicinal stereogenic centers; dual catalysis; synergistic catalysis